PENGARUH METODE TEAM QUIZ TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA SISWA KELAS VII SEKOLAH MENENGAH PERTAMA - Alamsyah; Hesti Noviyana (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2019)
The purpose of this study is to find the influence of a method of quiz the rest of the team in the ability of the math problem solving a student of class vii the first half the even junior high school nusantara bandar lampung. This study uses experimental methods with a population of all students vii of the junior high school nusantara. bandar lampung. Were selected from consisting of two classes; viia class as a class the experiment was a total of 32 students and class viib as a class control which consisted of 32 student. Samples taken by using clusters of random sampling. The ability of problem solving students dites using tests essays about 10 about who first tested validity and reliabilitasnya.The testing of hypotheses uji-t. it uses in research. Based on the results of the data analysis using formulas t-tes obtained t-hit = 2,85, from table distribution t the first significant 5 % known t = 1,67 test criteria thit > tdaf; t-daf hypothesis Ho rejected, means Ha accepted, so it can be concluded there an effect the application of a method of the rest of the team in the ability of the quiz the solution of the problems mathematics to their students class vii the even junior high school nusantara bandar lampung in 2016/2017.